Identification of Health Knowledge of Lung Function in Predicting Respiratory Disorders in Smokers - Amelia Lorensia; Rivan Virlando Suryadinata; Lalita Tirsa (Universitas Islam Bandung, 2021)
Chronic obstructive pulmonary disease (COPD) is a high risk for active smokers. Early assessment of the condition of lung function is needed to prevent a decrease in lung function. Knowledge of self-management that determines lung health. The purpose of this study was to determine the knowledge of lung function health in predicting respiratory disorders. The study design was a case-control from August 2018 to January 2019. Data was collected through a questionnaire, namely a lung health knowledge questionnaire consisting of categories: risk factors, symptoms, and therapy for respiratory disorders. The research sample was adult men who work in the transportation sector in Surabaya city using purposive sampling. Data analysis using chi-square. The data obtained were 300 people, consisting of 126 people without lung function disorders and 174 people with pulmonary function disorders. The risk factor knowledge category showed a significant difference (p=0.000) between the group, with the most disorders at the low knowledge level (42.0%). The symptom knowledge category showed a significant difference (p=0.000) between groups, and most of the groups with disorders were at a low knowledge level (55.8%). The category of knowledge of respiratory symptoms showed a significant difference (p=0.000) between groups, with the knowledge level in both of them mostly at a sufficient level. Therefore, low lung function health knowledge reflects low lung function conditions. IDENTIFIKASI PENGETAHUAN KESEHATAN FUNGSI PARU DALAM MEMPREDIKSI GANGGUAN PERNAPASAN PADA PEROKOKPenyakit paru obstruktif kronik (PPOK) berisiko tinggi dialami oleh perokok aktif. Pengkajian dini terhadap kondisi fungsi paru diperlukan untuk mencegah penurunan fungsi paru. Pengetahuan tentang manajemen diri yang menentukan kesehatan paru. Tujuan penelitian ini adalah mengetahui pengetahuan kesehatan fungsi paru dalam memprediksi gangguan pernapasan. Desain penelitian adalah case-control dari Agustus 2018 hingga Januari 2019. Pengumpulan data dilakukan melalui kuesioner, yaitu kuesioner pengetahuan kesehatan paru yang terdiri atas kategori: faktor risiko, gejala, dan terapi gangguan pernapasan. Sampel penelitian adalah laki-laki dewasa yang bekerja di sektor transportasi di Kota Surabaya dengan menggunakan purposive sampling. Analisis data menggunakan chi-square. Data yang diperoleh sebanyak 300 orang, terdiri atas 126 orang tanpa gangguan fungsi paru dan 174 orang dengan gangguan fungsi paru. Kategori pengetahuan faktor risiko menunjukkan perbedaan yang bermakna (p=0,000) antarkelompok dengan gangguan terbanyak pada pengetahuan tingkat rendah (42,0%). Kategori pengetahuan gejala menunjukkan perbedaan yang bermakna (p=0,000) antarkelompok dan sebagian besar kelompok dengan gangguan berada pada pengetahuan tingkat rendah (55,8%). Kategori pengetahuan gejala pernapasan menunjukkan perbedaan yang bermakna (p=0,000) antarkelompok dengan tingkat pengetahuan keduanya sebagian besar pada tingkat cukup. Oleh karena itu, pengetahuan kesehatan fungsi paru yang rendah mencerminkan kondisi fungsi paru yang rendah.